Modification of the chemico-physical properties of sewage sludge towards its application for agricultural purposes (Global Journals of Research in Engineering, 2012)
Municipal sewage sludge belongs to organic waste rich in organic matter nitrogen and phosphorus and at the same time poor in potassium content From the environmental viewpoint sewage sludge should be recovered as fertilizer i e utilised for land applications However in order to do so the sludge cannot contain heavy metals in amounts above the permitted levels The article presents the results of a research carried out to investigate the potential of utilizing sewage sludge of high fertilizing values and elevated zinc content for agricultural purposes by mixing it in appropriate ratio with fly ash from lignite and hard coal combustion and granulation Data from tests on enriching the sludge-fly ash mixtures with potassium to improve its fertilizing properties are also presented The research was carried out taking into account relevant regulations effective in the EU countries The investigations proved that sewage sludge can be successfully mixed with fly ash in weight proportion 1 1 and granulated while maintaining the minimum content of organic matter nitrogen and phosphorus required for organic-mineral fertilizers and meeting the level of heavy metals permissible for sludge used for agricultural purposes However due to low potassium content in sludge-fly ash mixtures an addition of potassium salt is proposed at maintaining simultaneously the proportion of sludge to ash as 7 3 The procedure for utilizing sewage sludge a problem-causing organic waste described in the paper shows that it is possible to produce an organic-mineral product of desired chemical properties for soil conditioning which through the granulation process acquires also a physical form and mechanical properties making it easy to transport and apply
Keywords: sewage sludge; fly ash; modification; agriculture